Rekonstruksi Laporan Keuangan Syariah: Prinsip, Kualitas Informasi, Dan Pengungkapan Pada Bank Syariah Indonesia - Putri, Adelia Nindya; Abdullah, Wahyuddin; Muchlis, Saiful (Jurnal Akuntansi & Keuangan Unja, 2026)
This article examines the reconstruction of Islamic financial statements, focusing on the application of accounting principles, information quality, and disclosure at Bank Syariah Indonesia (BSI). The study employed a descriptive qualitative method with a literature review approach, analyzing BSI's financial statements for the 2021-2025 period and related regulations. The results indicate that the reconstruction of Islamic financial statements requires a robust conceptual framework based on Islamic PSAK and AAOIFI standards to ensure transparency and accountability. Sharia principles serve as the foundation for recognizing, measuring, and presenting financial transactions, distinguishing Islamic accounting practices from conventional ones. The quality of Islamic financial statement information is determined by relevance, reliability, comparability, and timeliness of presentation. Comprehensive disclosures cover aspects of Islamic compliance, social funds, and operational risks, which are essential stakeholder needs. Bank Syariah Indonesia, the result of a business combination of three state-owned Islamic banks, applies the pooling of ownership method in preparing its financial statements, with adequate disclosures related to the business combination transaction. The reconstruction of sharia financial reports makes a significant contribution to increasing public trust, strengthening financial governance, and achieving the objectives of maqashid sharia in the Indonesian sharia banking industry.